2017
DOI: 10.1016/j.heliyon.2017.e00389
|View full text |Cite
|
Sign up to set email alerts
|

Selecting pure-emotion materials from the International Affective Picture System (IAPS) by Chinese university students: A study based on intensity-ratings only

Abstract: There is a need to use selected pictures with pure emotion as stimulation or treatment media for basic and clinical research. Pictures from the widely-used International Affective Picture System (IAPS) contain rich emotions, but no study has clearly stated that an emotion is exclusively expressed in its putative IAPS picture to date. We hypothesize that the IAPS images contain at least pure vectors of disgust, erotism (or erotica), fear, happiness, sadness and neutral emotions. Accordingly, we have selected 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 49 publications
0
13
0
1
Order By: Relevance
“…Then, we constructed and validated the basic structures of musical emotion by conducting both EFA and CFA on the intensity ratings. Actually, in this way, the investigators have successfully delineated the structures of facial expressions of emotion24 and picture vectors of emotion 25. In the current study, we have hypothesized that musical emotion at least includes happiness, tenderness, sadness, anger, and anxiousness and these emotions have their discriminant and convergent validities, since previous documentation had indicated that these emotions are the basic ones related to music 17,26.…”
Section: Introductionmentioning
confidence: 82%
“…Then, we constructed and validated the basic structures of musical emotion by conducting both EFA and CFA on the intensity ratings. Actually, in this way, the investigators have successfully delineated the structures of facial expressions of emotion24 and picture vectors of emotion 25. In the current study, we have hypothesized that musical emotion at least includes happiness, tenderness, sadness, anger, and anxiousness and these emotions have their discriminant and convergent validities, since previous documentation had indicated that these emotions are the basic ones related to music 17,26.…”
Section: Introductionmentioning
confidence: 82%
“…Although this observation was incidental to the main aims of the current study, this relative deficiency highlights the importance of better understanding the qualitative features that may make the emotional content of some social scenes less open to dispute. Researchers have previously cautioned that findings from experiments where complex scenes are assigned to emotion-eliciting conditions without procedures to validate their emotional content should be interpreted conservatively ( Barke et al, 2011 ; Moreno et al, 2016 ; Xu et al, 2017 ). Current findings suggest this caveat may apply in particular to social scenes.…”
Section: Discussionmentioning
confidence: 99%
“…However, while facial expressions of basic emotions are more likely to be categorized homogeneously among healthy individuals ( Wegrzyn, Vogt, Kireclioglu, Schneider, & Kissler, 2017 ), qualitative judgments of the same scene can vary markedly from one person to the next ( Mikels et al, 2005 ). To ensure more precise experimental manipulation, some investigators have highlighted the need for a panel of judges beyond the research team to validate the emotional content of experimental stimuli ( Barke, Stahl, & Kröner-Herwig, 2011 ; Moreno, Quezada, & Antivilo, 2016 ; Xu et al, 2017 ).…”
mentioning
confidence: 99%
“…Después de conocer estos estudios que describe los estímulos aversivos que son capaces de activar el SD, ¿cómo podemos transformar esta información en estrategias de marketing?, las aseguradoras sin conocer las bases neurales del miedo, por años han utilizado en su publicidad escenas de choques, catástrofes naturales, enfermedades, incendios, entre otros estímulos aversivos que, de acuerdo con el IAPS (Xu, et al, 2017), tienen una valencia emocional negativa alta y son capaces de activar el SD. En el transcurso de los anuncios o del discurso de los agentes de seguros, el SD se va activando, generando ansiedad, temor, y otras emociones negativas, sin embargo, la solución y la tranquilidad para que nada de eso pase, la tienen ellos, al comprar sus productos, nada pasará.…”
Section: Los Dos Sistemas Del Marketingunclassified